Hack, Mash, & Peer: Crowdsourcing Government Transparency - Brito, Jerry (Science and Technology Law Review, 2008)
In order to hold government accountable for its actions, citizens must know what those actions are. To that end, they must insist that government act openly and transparently to the greatest extent possible. In the twenty-first century, this entails making its data available online and easy to access. If government data is made available online in useful and flexible formats, citizens will be able to utilize modern Internet tools to shed light on government activities. Such tools include mashups, which highlight hidden connections between different data sets, and crowdsourcing, which makes light work of sifting through mountains of data by focusing thousands of eyes on a particular set of data. Today, however, the state of government’s online offerings is very sad indeed. Some nominally publicly available information is not online at all, and the data that is online is often not in useful formats. Government should be encouraged to release public information online in a structured, open, and searchable manner. To the extent that government does not modernize, however, we should hope that private third parties build unofficial databases and make these available in a useful form to the public.